Opinions and satisfactions of online education: marmara university students as case of study - DERMAN, GİRAY SAYNUR (My University, 2022)
The rapid development in technology has led to the emergence of online education, which permits educational institutions to give courses online. During the Covid 19 crisis, it was the first time that online education was implemented at all academic levels. A mechanism was adopted by institutions and universities to plan and arrange the progress of the study by administrators and responsible, while the teachers are prepared for the task of following up the education of the students using a variety of methods and programs. There was a challenge on the possibility of success of online education and the extent to which educational institutions are ready to implement it, especially since some students and teachers are living that experience for the first time. With life returning to regular and face-to-face teaching in schools, it is necessary to know the students’ experience with online education compared to face-to-face education. This study aimed to investigate the opinion and satisfaction of students of Marmara University with online education. The study was conducted using cognitive theory and quantitative methods. Data were collected through a questionnaire that included Marmara University students and it was analyzed by SPSS frequency.

Teknolojideki hızlı gelişme, eğitim kurumlarının çevrimiçi kurslar sunmasına izin veren çevrimiçi eğitimin ortaya çıkmasına neden olmuştur. Covid 19 krizi sırasında ilk kez online eğitim tüm eğitim kademelerinde uygulandı. Yöneticiler ve sorumlular tarafından çalışmanın ilerleyişini planlamak ve düzenlemek için kurumlar ve üniversiteler tarafından bir mekanizma benimsenirken, öğretmenler çeşitli yöntem ve programlar kullanarak öğrencilerin eğitimlerini takip etme görevine hazırlanmıştır. Çevrimiçi eğitimin başarılı olma olasılığı ve eğitim kurumlarının onu uygulamaya ne ölçüde hazır olduğu, özellikle de bazı öğrenci ve öğretmenlerin bu deneyimi ilk kez yaşadıkları için bir zorluk vardı. Okullarda hayatın normale dönmesi ve yüz yüze eğitime geçilmesi ile birlikte öğrencilerin yüz yüze eğitime kıyasla online eğitim deneyimlerini bilmek gerekmektedir. Bu araştırma, Marmara Üniversitesi öğrencilerinin online eğitime yönelik görüş ve memnuniyetlerini araştırmayı amaçlamıştır. Çalışma bilişsel kuram ve nicel yöntemler kullanılarak yürütülmüştür. Veriler, Marmara Üniversitesi öğrencilerinin katıldığı bir anket aracılığıyla toplanmış ve SPSS frekansı ile analiz edilmiştir.
Keywords: Opinion; Satisfaction; Online Education; Marmara University Students; Görüş; Memnuniyet; Online Eğitim; Marmara Üniversitesi Öğrencileri